Jesse Stuart autograph note - Stuart, Jesse, 1906-1984.
Autograph note (Riverton, Ky.) in which Stuart conveys his best wishes to Ben Brown. Removed from a book titled, Un Anno di Politica Estera : Discorsi (1921), held in the Library of Congress General Collections.
Author and educator.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Brown, Ben; Authors, American; Authors; Educators